Early acquisition of figurative meanings in polysemous nouns and verbs - Ana Werkmann Horvat; Kristina Štrkalj Despot; Gordana Hržica (Language and Cognition)
Early research on the first language acquisition of figurative language indicated that figurative language comprehension and production skills develop relatively late, while recent studies contest this view. This study explores early production of metaphorical (e.g., shark meaning a rapacious crafty person) and metonymic (e.g., house meaning an organisation) meanings in English polysemous nouns and verbs by using the Braunwald corpus, which tracks a single child’s speech from the age of 1 year, 5 months to 7 years. We explore the initial production of these meanings, with respect to the age, order of acquisition and part of speech (noun vs. verb). Our study shows that children start using figurative meanings at a much earlier age than previously thought. In this early stage, metonymic meanings emerge earlier, while metaphorical meanings come a few months later. These findings challenge prior beliefs that children only develop figurative language skills at 3 years of age and show that it is not only the pre-figurative skills that develop early but also the production of very conventional types of figurative meaning, which might not necessarily require the completed development of the complex set of cognitive skills necessary for cross-domain comparison.